예비 영어교사 주도에 의한 영미시 평가표 제작 및 평가 수행에 관한 연구 - 이호(Lee Ho), 전소연(Jun So-yeon) (영어어문교육, 2011)
This study explored pre-service English teachers' participation in the development of a rubric and examined evaluation of their own English poetry. The current study would investigate: 1) the pre-service English teachers' perception as a rubric developer and self-evaluator, 2) the number of analytic area that the participants included in their rubrics and the scoring scheme that they designed in their rubrics, and 3) the inter-rater differences between self-assessemnt and expert-assessment across analytic areas. Twenty-four EFL learners participated in the current study. The researchers analyzed the learners' own English poetry, their field notes which contained the process of their writing, their rubrics, scores of self-assessment, and expert raters' scores. The results revealed that learners showed positive responses on learner-directed assessment, that 'content' is the most important area, and that inter-rater difference is small across all analytic areas.